Influence of Rainfall and Rainy day On Rubber Production 13, 16, and 19 years Old in Lima Puluh PT.Socfin Indonesia - Rangga Amris Harun; irsal Irsal; Jonis Ginting (Universitas Sumatera Utara, 2019)
One of determining factors of water supply for rubber plants are rain fall and rain day. Water supply for rubber in field is obtained from rainfall. The amount of water that doesn’t consistent give negative impact to the productivity of rubber. This research was to determine the effect of rainfall and rain day as well as the correlation of both on rubber production in plants aged 13, 16, 19 years. This research is done in Sei Baleh Estate PT. Socfin Indonesia Kebun Lima Puluh District Batubara Province of Sumatera Utara from October to Desember 2016. This reasearch used primary data available in company administration. Primary data for the purposes of data analysis includes latex production in 2010, 2011, and 2012; rainfall data and rain day monthly in 2009, 2010, and 2011. Analysis method used are double linier regression and correlation analysis. Model tested by classic asumption consists of normality test, heteroskedasticity test, multicollinearity, and autocorellations test by using statistic software SPSS.v.17 for windows. The regression analysis shows that rainfall and rain day variables don’t have significant influence to increased latex production of rubber plants aged 13 years and have significant influence to increased latex production of rubber plants aged 16 and 19 years . Rainfall and rain day affect latex production 14,2%; 99,8%; dan 99,9% of rubber plants aged 13, 16, 19 years. The correlation result in plants aged 13, 16, 19 years showed variable rainfall and rain day have a strong relationship (0,926) against the latex production. Keywords: lateks production, rainfall, rainy day.